Reduced graphene aerogels as energy efficient selective oil sorbents - Junaid Saleem; Moghal Zubair Khalid Baig; Usman Bin Shahid; Said Mansour; Gordon McKay (Energy Reports, 2022)
Graphene aerogels are widely used in the oil–water system as they possess high internal surface area and super-oleophilic properties. However, they tend to absorb water along with oil, and to overcome this problem; surface coatings are generally employed using expensive fluoro-silane compounds. It leads to an increase in production costs and environmental concerns. Herein, we report super-hydrophobic 3D graphene aerogels as selective oil sorbent for oil–water​ separation. The reduction of oxygen-containing functional groups on the surface of graphene aerogels has been studied and characterized with FTIR. The thermal treatment of up to 700 °C was carried out using an in-house flow system. The gases used to reduce graphene oxide aerogel are H2and N2with an optimized ratio of 5:95. The presence of H2significantly decreased the oxygen-containing functional groups in graphene aerogel. The increase in the C/O ratio results in higher uptake capacity due to higher surface area and pore volume. The thermal reduction yields a C/O ratio of 24:1, slightly higher than most reported values.